Micro-credentials in higher education: a review and bibliometric - Johan, Riche Cynthia; Rullyana, Gema; Susilana, Rudi; Emilzoli, Mario (Journal of Education and Learning (EduLearn), 2025)
The objective of this study is to conduct a comprehensive review of research on “Micro-credentials in higher education” by doing a bibliometric analysis of 85 journal articles published between 2015 and 2023, obtained from the Scopus database. This study focuses on quantifying the number of publications and citations, as well as examining subject areas, connections, universities, countries, and identifying the most productive and prominent researchers. Apart from that, this research also identifies research topics that researchers have been working on in recent years. The findings show that publications and citations have increased in the last three years. The United States, Australia, and Canada are the most productive countries on this topic. T. J. Newby is the most productive researcher, while the most influential writer is D. -K. Mah. TechTrends and The International Journal of Information and Learning Technology are the journals that publish the most research. The university that made the top contribution was Purdue University (United States). The results of data analysis show that collaboration between authors researching “Micro-credentials in higher education” still needs improvement. This research contributes as a basis for further research in enriching and developing knowledge about micro-credentials, especially in higher education.